Preventing head and neck injury - McIntosh, A. S.; McCrory, P. (British Journal of Sports Medicine, 2005)
A wide range of head and neck injury risks are present in sport, including catastrophic injury. The literature since 1980 on prevention of head and neck injury in sport was reviewed, focusing on catastrophic and brain injury and identifying the range of injury prevention methods in use. There have been few formal evaluations of injury prevention methods. Approaches that are considered, or have been proven, to be successful in preventing injury include: modification of the baseball; implementation of helmet standards in ice hockey and American football and increased wearing rates; use of full faceguards in ice hockey; changes in rules associated with body contact; implementation of rules to reduce the impact forces in rugby scrums. Helmets and other devices have been shown to reduce the risk of severe head and facial injury, but current designs appear to make little difference to rates of concussion. Research methods involving epidemiological, medical, and human factors are required in combination with biomechanical and technological approaches to reduce further injury risks in sport.